2004
DOI: 10.1002/pola.20447
|View full text |Cite
|
Sign up to set email alerts
|

Polymers based on benzyl methacrylate: Synthesis via atom transfer radical polymerization, characterization, and thermal stabilities

Abstract: Copolymerization and homopolymerization of benzyl methacrylate (BMA) and ethyl methacrylate (EMA) by the atom transfer radical polymerization method (ATRP) were performed at 90°C. ATRP of BMA was also carried out at 80, 100, and 110°C. The number-average molecular weight (M n ) and polydispersities decreased with temperature. When BMA units increased in the copolymer system, the M n values and polydispersities decreased (1.63 Ͻ M w /M n Ͻ 1.13). The homopolymers and poly(BMAco-EMA) were characterized by Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
(26 reference statements)
2
24
0
Order By: Relevance
“…The differences between starch FTIR spectrum and the FTIR spectra of copolymers are clearly observed. FTIR spectrum of starch shows the characteristic bands corresponding to the stretching vibrations of OH groups (the region of 3000-3600 cm -1 ), the stretching vibrations of C-H (at 2840-2930 cm -1 ), the stretching vibrations of C-O-H and the C-O-C (the region of 998-1150 cm -1 ) [34,35]. However, on the FTIR spectra of copolymers the appearance of additional bands is indicated.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between starch FTIR spectrum and the FTIR spectra of copolymers are clearly observed. FTIR spectrum of starch shows the characteristic bands corresponding to the stretching vibrations of OH groups (the region of 3000-3600 cm -1 ), the stretching vibrations of C-H (at 2840-2930 cm -1 ), the stretching vibrations of C-O-H and the C-O-C (the region of 998-1150 cm -1 ) [34,35]. However, on the FTIR spectra of copolymers the appearance of additional bands is indicated.…”
Section: Resultsmentioning
confidence: 99%
“…It may be suggested that a lactone ring forms by means of removing benzyl bromide at the chain end, as suggested in Scheme 2. This band is not observed in that of poly(BMA) synthesized under free-radical polymerization conditions [22]. Designed miktoarm star shaped copolymers made of poly[(-caprolacton)(-PCL)-cobenzyl methacrylate(BMA)] were synthesized by combining ring-opening polymerization (ROP), as was illustrated in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
“…Phloroglucin dihydrate (Aldrich) was dryed to remove dihydrat in vacuo (at 2 mmHg) at 120˚C. Benzyl methacrylate (BMA) was prepared by aid of literature [22]. So, BMA was synthesized by the reaction of benzyl alcohol and methacryloyl chloride at 60˚C -70˚C by using potassium carbonate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples have typical high molecular weights and molecular weight distributions in the range expected for conventional radical polymerization. Compared with statistical copolymers of BzMA prepared by radical polymerization in bulk [32] or PBzMA and statistical copolymers, prepared by atom transfer radical polymerization (ATRP) [33] it is obvious that in the present study the solution copolymerization Synthesis of the statistical copolymers. leads to rather narrow distributions.…”
Section: Statistical Copolymers Of Bzma With Deaemamentioning
confidence: 99%